(untitled) (Вісник: Міжнародні відносини, 2021)
It is widely known that in historic respect Mongolia became the only country that succeeded in times of Genghis Khan and his successors in the conquest of both China and huge lands of Slavic people. With the flow of time enormous Mongol Empire disintegrated and the state actor that was established in the place of it is forced to exist between former parts of the Empire that today belong to the list of the most powerful countries of the world in military and economic respects. The Mongolian foreign policy of balancing between China and the Russian Federation is very interesting topic of scientific research, since the study of it helps to understand the set of measures that allow relatively weak and isolated country preserving independence in such challenging geopolitical neighborhood.